PAGAN AND CHRISTIAN DUALISM IN THE CULTURE OF ANCIENT RUS (World Science, 2020)
Based on archaeological artifacts, this paper considers another side of Christian and pagan dual faith in the West of Ancient Rus. We analyze material evidence, namely petroglyphs, amulets and ornaments, proving that people still worshiped the pagan deity, Perun, after adoption of Christianity. We place an emphasis on the motif of hatchet which, according to archaic beliefs, is the symbol of weapon, thunder, lightning, heavenly fire and light. We also explore significance of Perun's worship among the princely elite and warriors during the period of forceful unification and defense of the Ruthenian lands.